Nuclear magnetic resonance spectra of two types of lignin - Fukushima, Romualdo Shigueo; Hatfield, Ronald Donald (Pesquisa Agropecuaria Brasileira, 2003)
Lignin content can be useful to estimate fiber digestion of forage plants. Quantitative determination of lignin by the spectrophotometric method presumes an efficient standard. The objective of this work was to evaluate, by the nuclear magnetic resonance (NMR), two lignins, one extracted with acetyl bromide (AcBrL) and another with acidic dioxane solution (DL), as standards in spectrophotometric analysis. Proton resonance revealed high presence of carbohydrates in the AcBrL residues. Because liquid chromatograph had already shown low contamination with carbohydrates in the DL samples, only carbon resonance, which is lengthier, but richer in details than proton resonance, was run on these lignin samples. The carbon resonance revealed typical peaks common to most lignins. NMR findings were harmonious with wet chemistry which revealed that the cell wall carbohydrates attached to AcBrL would possibly be cellulose whereas in the DL, the small carbohydrate components would come from pentosans. DL can be considered a better standard to the spectrophotometric analysis than AcBrL.